(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article describes the importance of pasture lands in the development of the livestock industry, the state and productivity of pasture lands in Uzbekistan, and the priorities for their effective use in the future.